2020
DOI: 10.1111/ctr.13782
|View full text |Cite
|
Sign up to set email alerts
|

Development of an objective, standardized tool for surgical assessment of deceased donor kidneys: The Cambridge Kidney Assessment Tool

Abstract: Quality assessment in kidney transplantation involves inspection to identify negative markers of organ quality. However, there is a paucity of evidence guiding surgical appraisal, and currently there is no evidence to differentiate important features from those that can be safely ignored. We propose a method to standardize surgical assessment and derived a simple rule to rapidly identify kidneys suitable for transplantation. Donor and recipient data were recorded alongside clinical outcomes in a prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…These results suggest that further work is required to refine the current grading scale. Recently, Ayorinde et al have developed a pre‐implantation, objective macroscopic scoring system (Cambridge Kidney Assessment Tool, CKAT) 14 . Of the variables included in their system, the quality of the Carrel patch and the perfusion grade were found to be independently associated with organ utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that further work is required to refine the current grading scale. Recently, Ayorinde et al have developed a pre‐implantation, objective macroscopic scoring system (Cambridge Kidney Assessment Tool, CKAT) 14 . Of the variables included in their system, the quality of the Carrel patch and the perfusion grade were found to be independently associated with organ utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous national registry studies have explored factors associated with retrieval damage of kidneys, but overlooked the effects of perfusion defects on organ utilization and outcomes 11,12 . Most transplant programs require the retrieving surgeon to comment on the QOP, 13 but it remains a poorly defined entity, with no validated categorization and/or quantification 14 . Studies have shown that considerable disagreement can exist in assessing QOP, even among experienced surgeons within the same center 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47] More accurate risk-assessment and prediction tools are urgently needed to support better organ offer decision-making on an individual level. [48][49][50] Organ offering schemes need further refinements to better match deceased donor kidneys and potential recipients. In 2019, the United Kingdom changed its deceased donor kidney offering algorithm to more effectively "longevity match" organs and potential recipients.…”
Section: Tablementioning
confidence: 99%
“…One area where AI may be particularly useful is in characterizing chronic injury in deceased donor kidneys that have been retrieved for transplantation. It is now widespread practice (up to 80% of retrieved kidneys in some US states) 16 to perform urgent preimplantation biopsy analysis of kidneys from elderly, “expanded criteria” deceased donors, in order to identify those kidneys that have no, or minimal, chronic injury, and that are therefore suitable for transplantation 14 , 17 – 23 . However, time and cost constraints, allied to a relative scarcity of specialist expertise, limit evaluation of preimplantation biopsies to a single slide.…”
Section: Goals Determine Which Capabilities To Prioritizementioning
confidence: 99%
“…Whichever approach is taken, ultimately the choice of which artery to score and how may remain ambiguous, and assessors could reasonably disagree. This has implications for determining the performance of the model against a perceived “gold standard.” Although this is not a problem limited to AI assessments, 22 regardless, AI models are expected to work well for all users, and designs that provide the highest quality insight into the decision-making process may therefore be favored. These should allow a human overseer to intuitively grasp and interact with model output.…”
Section: Gray Areas and Computing Judgmentsmentioning
confidence: 99%